ANALYSIS OF CHANGES SENSITIVITY IN SECTORAL EMPLOYMENT OPPORTUNITIES TO ECONOMIC GROWTH AND MINIMUM WAGES - Sulistiyanti; Nursiswati A.; Joesoef J.R.; Ariyani F. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
This study aims to analyze the differences in sensitivity to changes in employment opportunities in the agricultural, industrial and service sectors that occur due to changes in economic growth rates, wage rates and labor force participation rates in Indonesia. Analysis was performed using panel data regression method. The results of the analysis show that economic growth has a positive effect on employment opportunities in the industrial and service sectors, with a lower rate of change in employment opportunities than the rate of economic growth. This means that economic growth has not been sufficient to absorb labor growth in the industrial and service sectors. Economic growth has a negative effect on employment opportunities in the agricultural sector. The minimum wage rate has a positive effect on employment opportunities in agriculture, but has a negative effect on employment opportunities in the industrial sector, and has no significant effect on employment opportunities in the service sector.